Inhibitor of PD-1/PD-L1: a new approach may be beneficial for the treatment of idiopathic pulmonary fibrosis - Jie Tan; Qianfei Xue; Xiao Hu; Junling Yang (Journal of Translational Medicine, 2024)
Abstract Idiopathic pulmonary fibrosis (IPF) is a globally prevalent, progressive disease with limited treatment options and poor prognosis. Because of its irreversible disease progression, IPF affects the quality and length of life of patients and imposes a significant burden on their families and social healthcare services. The use of the antifibrotic drugs pirfenidone and nintedanib can slow the progression of the disease to some extent, but it does not have a reverse effect on the prognosis. The option of lung transplantion is also limited owing to contraindications to transplantation, possible complications after transplantation, and the risk of death. Therefore, the discovery of new, effective treatment methods is an urgent need. Over recent years, various studies have been undertaken to investigate the relationship between interstitial pneumonia and lung cancer, suggesting that some immune checkpoints in IPF are similar to those in tumors. Immune checkpoints are a class of immunosuppressive molecules that are essential for maintaining autoimmune tolerance and regulating the duration and magnitude of immune responses in peripheral tissues. They can prevent normal tissues from being damaged and destroyed by the immune response. While current studies have focused on PD-1/PD-L1 and CTLA-4, PD-1/PD-L1 may be the only effective immune checkpoint IPF treatment. This review discusses the application of PD-1/PD-L1 checkpoint in IPF, with the aim of finding a new direction for IPF treatment.